Dietary ecology of fossil Theropithecus: Inferences from dental microwear textures of extant geladas from ecologically diverse sites. Issue 99 (October 2016) - Shapiro, Amy E.; Venkataraman, Vivek V.; Nguyen, Nga; Fashing, Peter J.
Abstract: As the only extant graminivorous primate, gelada monkeys ( Theropithecus gelada ) offer unique insights into how hominins and other extinct primates with strong C4 isotopic signatures may have subsisted on graminoid-rich diets. Fossil Theropithecus species sharing a strong C4 signal (i.e., Theropithecus brumpti, Theropithecus darti, and Theropithecus oswaldi ) have been reconstructed as predominantly graminivorous and potentially in ecological competition with contemporaneous hominins. However, inferring the breadth and variation of diet in these species (and therefore hominins) has proven problematic. Understanding how ecological variation within extant geladas impacts microwear and isotopic signatures may contribute to reconstructions of diet in fossil Theropithecus . Here, we build on a recent study at an ecologically intact tall grass ecosystem (Guassa, Ethiopia) that expanded the known diversity of gelada diets by demonstrating lower reliance on graminoids, greater consumption of forbs, and greater dietary species richness than previously described at disturbed sites. We used dental microwear texture analysis to explore how dietary variation among extant geladas may inform our understanding of the diets of fossil Theropithecus . First, we compared the dental microwear textures of geladas at Guassa to those of geladas from other sites. The microwear textures of geladas at Guassa exhibited more complexity, less anisotropy, and more variance in anisotropy and heterogeneity, reflecting the greater dietary diversity of Guassa geladas. Comparing microwear texture variables among this expanded gelada sample to those for T. brumpti, T. oswaldi, and T. darti yielded no significant differences. These results raise the intriguing possibility that data on how ecological variation and diet impact dental microwear and (possibly) isotopic signatures in extant geladas can be used to reconstruct the diets of extinct theropiths and, more broadly, hominins with strong C4 isotopic signatures. We conclude that extant gelada populations offer a powerful analog for inferring dietary variation among predominantly graminivorous fossil primates.